2021
DOI: 10.2991/ijcis.d.210203.008
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Grasshopper Optimization Algorithm with Local Search for Solving Data Clustering Problems

Abstract: This paper proposes a hybrid approach for solving data clustering problems. This hybrid approach used one of the swarm intelligence algorithms (SIAs): grasshopper optimization algorithm (GOA) due to its robustness and effectiveness in solving optimization problems. In addition, a local search (LS) strategy is applied to enhance the solution quality and access to optimal data clustering. The proposed algorithm is divided into two stages, the first of which aims to use GOA to prevent getting trapped in local min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It is used to solve the single objective and multi objective optimization problems, and it was tested for constrained and unconstrained test functions. The results show that the GOA algorithm could provide very competitive results, the good robustness and the superior performance of this algorithm was confirmed compared with other optimization algorithms [14][15][16][17][18][19][20]. But, at the same time, the GOA algorithm has some shortcomings: (1) original linear convergence parameter causes the processes of exploration and exploitation unbalanced; (2) unstable convergence speed; and (3) easy to fall into the local optimum [21,22].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is used to solve the single objective and multi objective optimization problems, and it was tested for constrained and unconstrained test functions. The results show that the GOA algorithm could provide very competitive results, the good robustness and the superior performance of this algorithm was confirmed compared with other optimization algorithms [14][15][16][17][18][19][20]. But, at the same time, the GOA algorithm has some shortcomings: (1) original linear convergence parameter causes the processes of exploration and exploitation unbalanced; (2) unstable convergence speed; and (3) easy to fall into the local optimum [21,22].…”
Section: Introductionmentioning
confidence: 74%
“…The simulation results for the different best parameter values obtained by the GOA optimization algorithm are presented in Figures (8)(9)(10)(11)(12)(13)(14), where it becomes obvious that the search of this GOA algorithm converges quickly to the optimum values (optimal solution) of the proposed set of parameters of the buried pipeline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In (El-Shorbagy & Ayoub, 2021), El-Shorbagy and Ayoub integrated a local search (LS) strategy into GOA to solve the data clustering problem. The experimental results and statistical analysis confirmed that the combination between GOA and LS outperformed mentioned techniques in the work.…”
Section: Bairathi and Gopalanimentioning
confidence: 99%
“…e most popular hybrid SIAs are hybrid cultural-trajectory-based search [66], hybrid of the ant colony and firefly algorithms (HAFA) [67], hybrid harmony search-cuckoo search (HS/ CS) algorithm [68], hybrid particle swarm optimizationgenetic algorithm (PSO/GA) [69], hybrid krill herd-biogeography-based optimization (KHBBO) algorithm [70], hybrid cat swarm optimization (CSO) [71], hybrid tissue membrane systems (TMS) and the evolution strategy with covariance matrix adaptation (CMA-ES) [72], hybrid grasshopper optimization algorithm-local search (GOA/LS) [73], krill herd-differential evolution (KHDE) [74], hybrid grasshopper optimization algorithm-genetic algorithm (GOA/GA) [75], hybrid bat algorithm with harmony search (BHS) [76], etc.…”
Section: Introductionmentioning
confidence: 99%